Assessment of Bullet Impact and Failure Mechanism of Concrete Containing Polythene Aggregates - Syal Ankush; Tiwary Aditya Kumar (E3S Web of Conferences, 2024)
The time from the initial stage of existence on Earth, the war continued. In this concern, India’s DRDO (Defence Research and Development Organization) and OFB (Ordnance Factory Board) worked appreciatively to develop new protective gear against assault weapons. The main focus of bullet or blast proof structures is to safeguard the life of soldiers, their accessories and gears, along with confidential and classified acquittance, firearm and ammunition, and sensitive systems. Defence structures like bunkers and tranches were designed in such discipline to keep them active round-the-clock with heavy armoury and made functional near to Line of Control (LOC) and Line of Actual Control (LAC) which oppose the effect of highly intensive blast waves. In such a manner, field testing with different Indian assault rifles i.e. INSAS (Indian Small Arms System), SIG 716i (US origin), and INSAS LMG (Indian Small Arms System-Light Machine Gun) was made from different ranges starting from 50mts to 300 mts extreme. Such structures were designed to protect the safety of soldiers from the bump of bullet effect. Structures designed are very strong and durable with opposition to high lateral load and visible surfacing. Construction material used for building plays a foremost role. The investigation is based on unique and advanced ideas in designing the defence structures. The investigation elaborates on the difference between conventional designing and the special designing of defence structures, as the advanced concept of polythene aggregates performs better than ordinary concrete.